Chimney and stack inspection guidelines - Hertlein, Bernard H. (American Society of Civil Engineers, 2003)
"Chimney and Stack Inspection Guidelines assists owners in determining what level of inspection is appropriate to a particular chimney and provides common criteria so that all parties involved have a clear understanding of the scope of the inspection and the end product required."--BOOK JACKET.